Viability and functional recovery of pancreatic islet cells co-cultured with liver, salivary glands and intestine cells. Issue 12 (December 2016) - Qujeq, Durdi; Abedian, Zeinab
Graphical abstract: Highlights: Isolation of rat primary salivary gland, liver and intestinal cells were carried out. Islets co-cultured with rat primary salivary gland, liver and intestinal cells. Rats received co-cultured islets with primary salivary gland, liver and intestinal cells. Islet cells co-cultured with liver, salivary glands and intestine cells facilitate the injured islet to recover its function. This study demonstrated that co-culturing strategy is a novel method for the survival and improvement of islets. Abstract: This study aimed to examine the co-culturing of the rat islets with liver, salivary glands and intestine primary cells in vitro and in vivo models of islet injury. Viability of pancreatic islet cells co-cultured was determined using trypan blue. Glucose level was measured in vivo condition by glucose oxidase method. Insulin levels were also determined in vivo and in vitro conditions by ELISA method. The in vitro results of this study showed that pancreatic islet cells co-cultured with liver, salivary glands and intestine cells caused a significant rise in insulin level. These effects displayed the following hierarchy: liver > salivary glands > intestine. On day 28, the insulin level of rats exposed to alloxan decreased compared with the rats that received non-treated islet transplantation. However, the insulin level of rats exposed to alloxan that received co-cultured islets with liver cells, salivary gland cells and intestine cells increased when we compared with the rats that received non-treated islet transplantation. Islet-transplanted diabetic rats showed the preserved ability to regulate blood glucose levels throughout the study period, suggesting prolongation of islet graft survival. We investigate the possibility that the epithelial lining of the tissues provide viability and functional recovery of the injured pancreatic islet cells.